2009
DOI: 10.1007/s00125-009-1579-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exenatide on circulating glucose, insulin, glucagon, cortisol and catecholamines in healthy volunteers during exercise

Abstract: In non-diabetic participants given exenatide, blood glucose concentrations rise rather than fall during aerobic exercise with an associated greater catecholamine response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
2
17
1
Order By: Relevance
“…In contrast, the epinephrine response to reducing glucose concentration to 3.5 mmol/L was significantly reduced by lixisenatide treatment, whereas the epinephrine response to further reduction in glucose concentration to 2.8 mmol/L was not different between the treatments. A normal epinephrine response to deep hypoglycemia by lixisenatide treatment is supported by studies on GLP-1 (11), exenatide (12), and albiglutide (13), whereas the finding that lixisenatide reduces epinephrine levels at glucose levels of 3.5 mmol/L contrasts with the normal response at this level by exenatide (12) and albiglutide (13), and is in contrast with an increase in epinephrine levels by exenatide during exercise (32). Again, whether this characteristic is due to differences between the GLP-1 receptor agonists, differences in clamp technique, or differences between healthy subjects and subjects with type 2 diabetes treated with oral agents or basal insulin remains to be studied.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, the epinephrine response to reducing glucose concentration to 3.5 mmol/L was significantly reduced by lixisenatide treatment, whereas the epinephrine response to further reduction in glucose concentration to 2.8 mmol/L was not different between the treatments. A normal epinephrine response to deep hypoglycemia by lixisenatide treatment is supported by studies on GLP-1 (11), exenatide (12), and albiglutide (13), whereas the finding that lixisenatide reduces epinephrine levels at glucose levels of 3.5 mmol/L contrasts with the normal response at this level by exenatide (12) and albiglutide (13), and is in contrast with an increase in epinephrine levels by exenatide during exercise (32). Again, whether this characteristic is due to differences between the GLP-1 receptor agonists, differences in clamp technique, or differences between healthy subjects and subjects with type 2 diabetes treated with oral agents or basal insulin remains to be studied.…”
Section: Discussionmentioning
confidence: 96%
“…29 This is in line with previous findings, in which GLP-1 receptor agonists were shown to stimulate SNS activity, measured by heart rate variability, 30,31 or plasma catecholamine levels. 32 Although increased SNS activity is commonly associated with vasoconstriction, several studies have demonstrated that for the microcirculation, SNS activity might be associated with improved perfusion and consequently glucose uptake. 25 For example, in healthy volunteers, clamped hyperinsulinemia increased power in the neurogenic domain, which was associated with increased capillary perfusion and glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The function of carnitine in energy metabolism is impaired in diabetes and is also associated with increased lipolysis and the mobilization of free-fatty acids [71]. The metabolic response to exercise is closely regulated via circulating levels of counterregulatory hormones, such as catecholamines, glucagon and cortisol in response to fluctuations in blood glucose and insulin levels [72].…”
Section: Metabolic Hormonal and Autonomic Modulation Of Exercise In mentioning
confidence: 99%